Green product of Kusamba Salt: an Alternative of Re-Branding Strategy in Kusamba, Klungkung, Bali - LAKSMI, Putu Ayu Sita; PUTRI, Sukmasari Triana Gita; PURNAMAWATI, Ida Ayu Putu Santi; DEWI, Gusti Ayu Agung Istri Sari; JAMALUDDIN, Mohd Raziff Bin; RASHID, Wan Edura Wan; SAIHANI, Shamsul Bahrin (Indonesia Strategic Sustainability, 2024)
The Bali Government, recognizing the potential of Kusamba salt, has proposed a strategic plan to introduce it worldwide. The governor of Bali, Wayan Koster, suggested enhancing the marketing strategy to make Kusamba salt more appealing. This involves creating attractive packaging and promoting the product's unique qualities, such as its high-quality production methods and the environmental benefits of using natural Salt. Product Differentiation: The proposal emphasizes the need to differentiate Kusamba salt from other table salt products in the market. This could be achieved by highlighting the product's low iodine content, which benefits health and environmental sustainability. Market Integration: The plan also aims to integrate Kusamba salt into global markets. This involves identifying and establishing partnerships with international retailers and distributors interested in natural and health-conscious products. Farmer Empowerment: A significant part of the strategy focuses on empowering the salt farmers of Kusamba village. This includes facilitating the management of BPOM (Badan et al.) licenses and creating opportunities for the farmers to participate in the marketing and distributing their products. Environmental Sustainability: The proposal highlights the importance of promoting Kusamba salt as an environmentally friendly product. This could involve using eco-friendly packaging and promoting the product's sustainable production methods. In summary, the